Percy Jackson & the Olympians. The lightning thief. - Thurman, Uma.; Brosnan, Pierce; McKidd, Kevin; Bean, Sean.; Dawson, Rosario; Keener, Catherine; Lerman, Logan, 1992-; Jackson, Brandon T., 1984-; Daddario, Alexandra, 1986-; Abel, Jake, 1987-; Coogan, Steve; Columbus, Chris; et al. (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2010)
Percy Jackson is no ordinary teenager, he's the son of Poseidon and is accused of stealing Zeus' lightning bolt, the most powerful weapon ever created! Percy embarks on an incredible cross-country journey to prove his innocence, recover the bolt, and prevent a war among the gods that could destroy our world!
Based on the characters created by Rick Riordan.
Director of photography, Stephen Goldblatt ; editor, Peter Honess ; music, Christophe Beck.
Logan Lerman, Brandon T. Jackson, Alexandra Daddario, Jake Abel, Sean Bean, Pierce Brosnan, Steve Coogan, Rosario Dawson, Melina Kanakaredes, Catherine Keener, Kevin McKidd, Joe Pantoliano, Uma Thurman.
MPAA rating: PG; for action violence and peril, some scary images and suggestive material, and mild language.
DVD; region 1; widescreen (2.35:1) presentation; dual layer.
English, French, Spanish audio; English SDH, Spanish subtitles; closed-captioned.
Keywords: Jackson, Percy (Fictitious character) -- Drama; Teenagers -- Conduct of life -- Drama; Friendship -- Drama; Mythology, Greek -- Drama; Fantasy films; Feature films; Adventure films; Video recordings for the hearing impaired